Development of antibacterial paper coated with sodium hyaluronate stabilized curcumin-Ag nanohybrid and chitosan via polyelectrolyte complexation for medical applications. (3rd November 2017) - Kummara, Madhusudana Rao; Kumar, Anuj; Sung Soo, Han
Abstract: Sodium hyaluronate (HA) stabilized curcumin-Ag (Cur-Ag) hybrid nanoparticles were prepared in the water–ethanol mixture under constant mechanical stirring condition. The obtained HA stabilized Cur-Ag hybrid nanoparticles were characterized by fourier transform infrared spectroscopy, UV–visible spectroscopy, and x-ray diffraction to confirm the formation and structural interactions. The obtained Cur-Ag hybrid nanoparticles showed spherical shape with their size range 5–12 nm that was increased with the increasing a amount of silver ions as confirmed by transmission electron microscopic analysis. Further, a fibrous cellulose filter paper was impregnated with these hybrid nanoparticles and chitosan (CS) as biopolymer via polyelectrolyte complexation. The morphological analysis confirmed the uniform distribution of hybrid nanoparticle system onto the cellulose fibers of the fibrous filter paper. As per disc diffusion method, the Cur-Ag hybrid nanoparticles impregnated CS-coated filter paper exhibited excellent antibacterial properties against gram-negative Escherichia coli ( E.coli ) bacteria compared to HA stabilized Cur only. Moreover, as prepared hybrid nanoparticles impregnated biocomposite system is eco-friendly with efficient antibacterial property and have good potential to be used in medical applications.